Vazha Keshelava on relevant issues in contemporary politics - Darchashvili, Manana (Politics / პოლიტიკა; 2019: მესამე ნომერი, 2020)
Vazha Keshelava’s articles, published between 1993 and 2004, focus on actual issues in post-Soviet Georgia: separation of powers, presidential mandates, Rose Revolution, Russian-Georgian relations. etc.